Extraction, texture analysis and polysaccharide epitope mapping data of sequential extracts of strawberry, apple, tomato and aubergine fruit parenchyma - Cornuault VRG; Pose S; Knox JP (Elsevier)
The data included in this article are related to the research article entitled “Disentangling pectic homogalacturonan and rhamnogalacturonan-I polysaccharides: evidence for sub-populations in fruit parenchyma systems” (Cornuault et al., 2018) [1]. Cell wall properties are an important contributor to fruit texture. These datasets compile textural and immunochemical analysis of polysaccharides of four economically important fruit crops: tomato, strawberry, aubergine and apple with contrasting textures and related taxonomical origins. Cell wall components and their extractability were assessed using characterized monoclonal antibodies. In addition, textural data obtained for the four parenchyma systems show variations in the mechanical properties. The two datasets are a basis to relate cell wall composition and organization to the mechanical properties of the fruit parenchyma tissues.